2013
DOI: 10.1021/nl401952h
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Fe3O4 Nanoparticle Clusters as High-Performance Anodes for Lithium Ion Batteries via Geometric Confinement

Abstract: Although different kinds of metal oxide nanoparticles continue to be proposed as anode materials for lithium ion batteries (LIBs), their cycle life and power density are still not suitable for commercial applications. Metal oxide nanoparticles have a large storage capacity, but they suffer from the excessive generation of solid-electrolyte interphase (SEI) on the surface, low electrical conductivity, and mechanical degradation and pulverization resulted from severe volume expansion during cycling. Herein we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
239
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(252 citation statements)
references
References 44 publications
13
239
0
Order By: Relevance
“…It can be found that the CV curve of the NiO/CNTs microspheres is similar to that of NiO. In the first cycle, there are two obvious reduction peaks at about 0.95V and 0.55V, which is similar with the previous study [46]. The peak at 0.95V could be attributed to the conversion of NiO to Ni, and the peak at 0.55V should be resulted from the formation of SEI films.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…It can be found that the CV curve of the NiO/CNTs microspheres is similar to that of NiO. In the first cycle, there are two obvious reduction peaks at about 0.95V and 0.55V, which is similar with the previous study [46]. The peak at 0.95V could be attributed to the conversion of NiO to Ni, and the peak at 0.55V should be resulted from the formation of SEI films.…”
Section: Resultssupporting
confidence: 85%
“…From the second cycle, the columbic efficiencies of the electrode are more than 97.0%, which indicates the excellent reversibility of the electrodes. It is attributed to the formation of stable SEI films during cycles due to the microsphere composed of nanoparticles second structure [46] and the coated amorphous carbon.…”
Section: Resultsmentioning
confidence: 99%
“…These indicate that the 0.12 and 0.80 V plateaus most probably correspond to electrolyte decomposition and other SEI-forming processes, and that the higher voltage plateau is probably due to the ? of the first cycle in the dQ/dV curve are characteristic of the reduction of iron oxides (Fe 2 O 3 , Fe 3 O 4 ) and oxyhydroxides (FeOOH) in good agreement with which has been previously reported [23][24][25]. The electrochemical behavior of the as-deposited Fe-nanoparticles films is significantly different from that of the Fe-C films, which confirms our previous observations regarding the performance of the composite.…”
Section: Electrochemical Performancesupporting
confidence: 91%
“…Iron species such as Fe 2 O 3 , Fe 3 O 4 , and FeOOH can react electrochemically with Li ? providing extra capacity but suffering from pulverization and side reactions with the electrolyte [23][24][25]. Fe-C nano-composites (Fig.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…Their unique structures endow them with interesting properties, which promise diverse applications such as controlled delivery and release [6,7], magnetic separation [8,9], dye sensitized solar cells [10], lithium ion batteries [11,12], and noble metal catalysts [13]. To date, there are several methods to fabricate SPs in literature.…”
mentioning
confidence: 99%